KARAKTER PESERTA DIDIK DI ERA REVOLUSI 5.0 DI INDONESIA - A, Apdoludin; Putra, Randi Eka; Hakiki, Muhammad; Utama, Refli Surya (Information Technology Education Department, 2023)
The problem in this study is the lack of attention from people to learning behavior and the public who are less sensitive to the character of students, this is due to a lack of encouragement from people around students. The purpose of this study was to determine the positive role of the environment on the character of elementary school students in Muara Bungo. This research is a type of qualitative research. The subjects of this study were elementary school students in Muara Bungo as many as 4 students, as well as 3 parents, 2 teachers and 4 additional informants as samples. Data collection techniques are observation, documentation and interviews. Data analysis techniques in this study are in the form of data collection, data reduction, data display and conclusions. The findings of this study are that the role of a positive environment can affect the character of students to be positive and the environment plays a very important role in the growth and development of students, therefore people who are in the environment of students must maintain harmony and protect students in a good direction.